LaRue across America : postcards from the vacation - Teague, Mark. (New York : Blue Sky Press, 2011)
Mrs. LaRue takes a cross-country drive with her hospitalized neighbor's cats and her own dog, Ike, who keeps the cats' owner informed of their misadventures through a series of postcards.
Map on endpapers.
Kirkus Starred
Publisher's Weekly
School Library Journal
Kirkus Starred, February 2011
Publisher's Weekly, January 2011
Keywords: Automobile travel -- Juvenile fiction; Cats -- Juvenile fiction; Dogs -- Juvenile fiction; Postcards -- Juvenile fiction; Automobile travel -- Fiction; Cats -- Fiction; Dogs -- Fiction; Humorous stories; Postcards -- Fiction; Automobile travel -- Fiction; Cats -- Fiction; Dogs -- Fiction; Humorous fiction; Postcards -- Fiction; Humorous fiction; Picture books for children